2015
DOI: 10.1016/j.ijid.2015.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Complications of Pulmonary Tuberculosis, including Drug-Resistant Tuberculosis

Abstract: Surgery for drug-resistant tuberculosis has been shown to be safe and effective, with similar level of mortalities associated with surgical intervention observed with that for lung cancer. While surgery has been an option to treat TB in the pre-antibiotic era, it is now increasingly used to treat complications of pulmonary TB, particularly in patients with drug-resistant TB who do not respond to medical treatment. The two most frequent indications for lung resection in drug- resistant TB, are i) failed medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 27 publications
3
31
0
2
Order By: Relevance
“…This supports the call for more interaction between cardiothoracic surgeons and pulmonary physicians to identify at an early stage patients who may benefit from surgery [11]. Similar to findings in our series, other authors have also reported haemoptysis as the commonest indication for intervention in patients with TB, although they intervened earlier with emergency surgeries in cases of massive haemoptysis [5,9,12].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This supports the call for more interaction between cardiothoracic surgeons and pulmonary physicians to identify at an early stage patients who may benefit from surgery [11]. Similar to findings in our series, other authors have also reported haemoptysis as the commonest indication for intervention in patients with TB, although they intervened earlier with emergency surgeries in cases of massive haemoptysis [5,9,12].…”
Section: Discussionsupporting
confidence: 90%
“…We used a double-lumen tube to achieve one-lung ventilation for all our lung resections to improve exposure and protect the contralateral lung from soilage [14]. We placed 2 of our patients on anti-TB therapy in line with postoperative histological diagnosis because the effect of TB is usually beyond the resected lungs [5,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations